2018
DOI: 10.24912/jmieb.v1i2.962
|View full text |Cite
|
Sign up to set email alerts
|

Organisasi Pembelajaran, Kompetensi Dan Kinerja Karyawan Bank XXX Di Jakarta

Abstract: This study aimed to determine empirically learning organization have affect to competence, competence have significant affects to performance, learning organization through competence have significant affect to performance. The method used in sampling was simple random sampling, a total of  200 employee at Bank “XXX” in Jakarta The data analysis technique used is Structural Equation Modeling (SEM), using by LISREL versi 8.8 are need to test the hypothesis. The results showed, learning organization give effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Zhang et al mentions organizational commitment as the alignment and loyalty of employees to the organization and organizational goals [11]. The results of this study are also still being debated, causing a research gap; Rahardjo & Purwanto found organizational commitment has a significant effect on employee performance [8]. However, research by Gielhan Abraham Rembet et al, organizational commitment has no significant effect on employee performance [12].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Zhang et al mentions organizational commitment as the alignment and loyalty of employees to the organization and organizational goals [11]. The results of this study are also still being debated, causing a research gap; Rahardjo & Purwanto found organizational commitment has a significant effect on employee performance [8]. However, research by Gielhan Abraham Rembet et al, organizational commitment has no significant effect on employee performance [12].…”
Section: Introductionmentioning
confidence: 87%
“…However, there are still many studies that give different results so that it is still a debate, causing a research gap. Basori, Rahardjo & Purwanto found that organizational learning has a significant effect on employee performance, but Purnamasari's research, organizational learning has no significant effect on employee performance [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Kegiatan belajar mengajar akan lebih hidup dengan model kooperatif karena di dalamnya aktif dalam diskusi dan dilatih berfikir kritis. "Model Pembelajaran Cooperative diyakini dapat memberi peluang peserta didik untuk terlibat dalam diskusi, berfikir kritis, berani dan mau mengambil tanggung jawab untuk pembelajaran mereka sendiri" (Rahardjo, 2012). Usaha-usaha guru dalam membelajarkan siswa merupakan bagian yang sangat penting dalam mencapai keberhasilan tujuan pembelajaran yang sudah direncanakan.…”
Section: Hasil Dan Pembahasan Model Pembelajaran Kooperatif Jigsawunclassified
“…Dengan pembelajaran organisasi yang baik dan cepat dalam menerima informasi akan menghasilkan peningkatan dalam kualitas kinerja organisasi. Penelitian dilakukan sebelumnya menunjukkan bahwa pembelajaran organisasional berpengaruh terhadap kinerja (Basori, 2017;Darmanto & Ariyanti, 2021;Pratiwi et al, 2020;Purwanto et al, 2020;Rahardjo & Purwanto, 2018;Winarno & Sri, 2020). Oleh karena hipotesis yang diajukan adalah : H2: Pembelajaran organisasional berpengaruh positif terhadap kinerja organisasi Berpijak dari teori RBT bahwa perusahaan sebagai kumpulan sumber daya dan kemampuan maka variable yang diteliti dalam studi ini untuk menjelaskan mengenai masalah kinerja perusahaan menggunakan pendekatan variable yang bersumber dari kapabilitas internal perusahaan.…”
Section: Pengembangan Hipotesisunclassified